2017
DOI: 10.1111/dmcn.13438
|View full text |Cite
|
Sign up to set email alerts
|

Sucking behaviour in infants born preterm and developmental outcomes at primary school age

Abstract: Abnormal sucking between 42 weeks and 50 weeks postmenstrual age may reflect abnormal neurological functioning in children born preterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Thus, early NNS patterning can serve as an early marker of neonatal brain function. In addition to indicating current brain function, emerging data is available linking neonatal NNS to subsequent neurodevelopment [18]. More specifically, neonatal NNS has been associated with total motor skills, balance, total intelligence, verbal intelligence, performance intelligence, and language at age five, with better neonatal NNS relating to higher test scores [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early NNS patterning can serve as an early marker of neonatal brain function. In addition to indicating current brain function, emerging data is available linking neonatal NNS to subsequent neurodevelopment [18]. More specifically, neonatal NNS has been associated with total motor skills, balance, total intelligence, verbal intelligence, performance intelligence, and language at age five, with better neonatal NNS relating to higher test scores [18].…”
Section: Introductionmentioning
confidence: 99%
“…A total of fourteen distinctive instruments were applied before 5y: GmA[26e39], Bayley Scales of Infant Development (BSID) [36,40e48], MOS, Peabody Developmental Motor Scales (PDMS) [49e51], Alberta Infant Motor Scale (AIMS) [47,48], Motor subtests of the Griffiths Mental Development Scales (GMDS) [50,52], Ages and Stages Questionnaire (ASQ) [53,54], Movement Assessment Battery for Children (M-ABC) [55], Neurological, Sensory, Motor, Developmental Assessment (NSMDA) [56], Motor scale of the Neonatal Behavioral Assessment Scale (NBAS), Combined Assessment of Motor Performance and Behavior (CAMPB) [57], Neonatal Oral-Motor Assessment Scale (NOMAS) [58] and NEPSY Copy Design Task [54]. Seventeen studies reported motor assessments before 6 months (m) [26e35,37e40, 43,44,48,53,58], fifteen between 6m and 2y [36,40e44,46e53,56] and eight between 2 and 5y [45,49,50,53e57]. Within the baseline assessment age of this review (before 5y), eight studies evaluated children twice [26,30,32,33,36,38,41,50,52], seven studies evaluated children three times [27,28,30,40,42,46,47,56], and six studies evaluated children four times or more [36,43,44,48,...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seventeen studies reported motor assessments before 6 months (m) [26e35,37e40, 43,44,48,53,58], fifteen between 6m and 2y [36,40e44,46e53,56] and eight between 2 and 5y [45,49,50,53e57]. Within the baseline assessment age of this review (before 5y), eight studies evaluated children twice [26,30,32,33,36,38,41,50,52], seven studies evaluated children three times [27,28,30,40,42,46,47,56], and six studies evaluated children four times or more [36,43,44,48,51,58]. Outcome measures were defined as (probable) DCD in four studies, cMND in five studies and significant motor delay on a standardized assessment in 23 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prognostic significance of abnormal sucking behaviour in infants born preterm remains a subject of debate. The paper by Wolthuis‐Stigter et al . provides a valuable contribution to this discussion, investigating the predictive relation between a standard measure of early sucking behaviour and later neurodevelopmental outcomes, including cognitive and language measures at school age.…”
mentioning
confidence: 99%